Language use variation of L2 writers in weblog across different gender and genres (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Despite the growing interest in investigating learners’ corpora, surprisingly little research has been conducted on the language use of L2 writers and its relation to the gender and genres in writing. Therefore, this study was aimed to find out the variation of language use in different genres or gender in weblogs, one of popular modes of computer-mediated communication (CMC). The study was done by conducting multivariate analysis using R program to weblog entries from a sample balanced of author gender (female or male) and weblog genre (diary or filter). Taking linguistic preferential features by Argamon et al (2003) and Pennebaker (2011) as dependent variables, the effect of genres or gender toward the use of the features was analyzed. The results showed that significant effects of several features can be considered as predictors. Personal pronouns and hedges (I think, and I believe) were found as predictors for diary; while the indefinite articles a/an and numbers were found as predictors for filter. As for the different language use by gender, female predictors were personal pronoun, verbs, negation, certainty words, and hedges. Meanwhile, the indefinite articles a/an, numbers, and preposition were the predictors of male writers.